Identity, material culture and tourism: Of ritual cloths and totem poles. (June 2017) - King, Victor T
In this study of the relationships between identity, material culture and tourism some of the different roles of the anthropologist in engaging with the wider field of cultural identity are examined. It commences with the approach of the conceptually-oriented anthropologist in addressing issues of culture, identity and ethnicity. Then it explores the role of the anthropologist in an applied mode with regard to the ritual cloths of the Iban of Sarawak, Malaysia. It argues for the importance of advocacy and persuading governments to acknowledge the importance of material emblems of identity and to ensure that indigenous knowledge and skills are sustained and contribute to local livelihoods. Finally the study considers the anthropologist as tourist and the ways in which an informed mode of travelling, in this case engaging with North-west Coast American/Canadian Indian totem poles, can contribute to the development of a comparative anthropology of tourism. It is argued that comparisons between Sarawak and the North-west Coast in the context of issues of identity, material culture and tourism can contribute to an understanding of the ways in which items of material culture are deployed and transformed in globalising processes of identity construction and transformation.